MBR 공정에서 CODcr 부하에 따른 막의 여과저항 변화와 세정효과 - 이준명; 최창규; 이광호 (한국수처리학회지, 18(6), 2010)
The research evaluated an effect on the membrane fouling with passive adsorption and permeability resistance according to the relatively low CODcr loading rates(0.13, 0.27 and 0.40kgCODcr/㎥/day), and investigated the recovery rate of permeability by rinsing, backwashing and chemical cleaning and EPS(Extracellular polymeric substances) concentration within a reactor in submerged membrane bioreactor. As a result, high CODcr loading rate accelerated the membrane fouling, and the increase of foulants(protein and carbohydrate) affected the membrane fouling rather than the MLSS. The increased permeability resistance was completely recovered by rinsing within 14 days from the beginning, however, the chemical cleaning was much proportion for the resistance recovery after 21 days. Thus the chemical cleaning could achieve an important role as the MBR process would continuously operate. Also, the concentrations of protein and carbohydrate in eEPS was higher than thoes in sEPS, we found that protein and carbohydrate was mainly adhisive on the surface of microbe. The research evaluated an effect on the membrane fouling with passive adsorption and permeability resistance according to the relatively low CODcr loading rates(0.13, 0.27 and 0.40kgCODcr/㎥/day), and investigated the recovery rate of permeability by rinsing, backwashing and chemical cleaning and EPS(Extracellular polymeric substances) concentration within a reactor in submerged membrane bioreactor. As a result, high CODcr loading rate accelerated the membrane fouling, and the increase of foulants(protein and carbohydrate) affected the membrane fouling rather than the MLSS. The increased permeability resistance was completely recovered by rinsing within 14 days from the beginning, however, the chemical cleaning was much proportion for the resistance recovery after 21 days. Thus the chemical cleaning could achieve an important role as the MBR process would continuously operate. Also, the concentrations of protein and carbohydrate in eEPS was higher than thoes in sEPS, we found that protein and carbohydrate was mainly adhisive on the surface of microbe. KCI Citation Count: 5